MODERNIZATION TENDENCIES OF PROFESSIONALLY-PSYCHOLOGICAL PREPARATION OF DOCTORS: COMPETENCE APPROACH - Lazurenko, Olena (PSYCHOLOGICAL JOURNAL, 2018)
The article studies psychological and pedagogical components of the psychological competence formation of future doctors at different phases of training. Main aspects of future doctors’ professional training at higher medical educational institutions are also described. Author attempts to disclose the specifics of future specialist’s psychological competence formation. The concept of professionally-psychological aspects of doctor’s preparation is suggested. The problem of the formation of psychological competence of future doctors is one of the most important in the field of professional medical education. Analysis of state educational standard of higher medical education has shown that some of the disciplines hereunder, allow students to obtain information about the psychological aspects of the emotional sphere, the emotional organization of personality, age-related peculiarities of this phenomenon, as well as the basics of control of emotional states. The results of the analysis of curricula and training programs of medical specialists indicate that the psychology is not a separate object of pedagogical influence, and therefore there is an objective contradiction between the real needs of the future specialist in acquisition of knowledge on the psychology of emotions and the ability to get them in the learning process in higher medical schools. The results of our analysis allowed us to establish that today the problem of the formation of psychological competence of a future specialist is new in the field of psychological research. However, in our deep conviction, it is advisable to figure out how to solve this problem in practice, at higher medical education. The research of psychological features of the future doctor psychological competence and analysis of its structural components are presented in the article. Based on the results of a search phase of the study of the formation of psychological competence of future doctors, tasks were identified and hypothesized pilot study. On the basis of generalization of the obtained results identify ways of promoting professional competences. Set out the overall strategy, the structure, revealed the main principles, methodological approaches and content of training programs aimed at developing the psychological competence of students – future doctors.